Studying Public Relations Behaviors in the Performance of Public Relations and Social Trust (The Case Study: Banks of Khuzestan Province) - mahdi nadaf; bdolhadi Darzian Azizi; zeynab masoudi (توسعه اجتماعی)
The aim of this study was to studying the relationship between public relations (PR) management behaviors with PR performance and PR performance with social trust. The sample in this study consisted of public relations managers and experts who were selected completely among banks of Khouzestan province. Data are collected by questionnaires as follows: questionnaire of public relations (PR) management behaviors, PR performance questionnaire and social trust questionnaire. Correlation test, Regression test, independent-samples T test and structural equation modelling (SEM) were performed using software SPSS and AMOS. The tested model in sample had a good fit. Results indicated that public relations management behaviors have significant influence on PR performance. Also results shows that public relations performance have significant influence on social trust.